Low-Cost Printed Flexible Antenna by Using an Office Printer for Conformal Applications - Kashif Nisar Paracha; Sharul Kamal Abdul Rahim; Hassan Tariq Chattha; Saqer Saleh Aljaafreh; Sabih ur Rehman; Yew Chiong Lo (International Journal of Antennas and Propagation)
A low-cost inkjet printing method for antenna fabrication on a polyethylene terephthalate (PET) substrate is presented in this paper. An office inkjet printer is used to have desired patterns of silver nanoparticle ink on the PET substrate without any postprocessing. Silver nanoparticle ink cures instantly as soon as it is ejected from the printer on a chemically treated PET substrate. The thickness of the silver nanoparticle layer was measured to be 300 nm with a sheet resistance of as low as 0.3 Ω/sq and a conductivity around 1.11 × 107 S/m with single layer deposition. A coplanar waveguide- (CPW-) fed Z-shape planar antenna on the PET substrate achieved the measured radiation efficiency of 62% and the IEEE gain of 1.44 dBi at 2.45 GHz. The printed antenna is also tested in bending conditions to ascertain its performance for the Internet of things (IoT) conformal applications for the future 5G network.